Distribution of Coronary Artery Anomalies and Their Evaluation with Different Imaging Modalities - Abhishek Raval; Nikhi Jadhav; Jayesh Prajapati; Jayesh Rawal; Rajiv Garg; Komal Shah; Iva Patel (International Journal of Medical Research and Review, 2019)
Introduction: Coronary artery anomalies (CAA) are diverse abnormalities.Methods: A retrospective review of coronary imaging of 17,245 patients over 2 years was performed. Patients with CAA detected on echocardiography, invasive coronary angiography (CAG) and multidetector computed tomographic angiography (MDCTA) were compared.Results: CAAs were detected in 257 patients (1.49%). Prevalence were: absent left main trunk- 0.319%, anomalous coronary artery from opposite sinus (ACAOS)- 0.516%, coronary fistulae- 0.203%, myocardial bridge- 0.093%, malignant anomalies- 0.3%. The commonest CAA was absent left main trunk. The yield of echocardiography negatively correlated with age (r=-0.6). CAG and MDCTA were equal (p=1) for detection of absent left main trunk. CAG had low sensitivity (58.3%) and MDCTA was better than it (p<0.01) for detection of abnormal high origin. For ACAOS, detection by both were not different (p=0.5) but the course was delineated better with MDCTA than with CAG (p=0.05). Both were equal for detection of intramyocardial course (p=0.5). However, MDCTA delineated its course better than CAG (p<0.01). Echocardiography had 93% sensitivity for fistula in those <12 years in age. Radiation exposure with CAG, 7.3 ± 2mSv, was lower than that with MDCTA, 14.5 ± 3mSv (p<0.01). It correlated with CAA score (r=0.3), with CAG but not with MDCTA. Contrast exposure correlated with CAA score (r=0.4) for adults with CAG but not with MDCTA.Conclusion: Echocardiography reliably detects CAAs in children. CAG and MDCTA are comparable for detection of most CAA. MDCTA delineates the course better than CAG. For MDCTA, radiation exposure is not correlated with complexity of CAA in contrast to that with CAG.